Public Hospital Spending in England: Evidence from National Health Service Administrative Records1. (September 2016) - Kelly, Elaine; Stoye, George; Vera‐Hernández, Marcos
Abstract: Health spending per capita in England has almost doubled since 1997, yet relatively little is known about how that spending is distributed across the population. This paper uses administrative National Health Service (NHS) hospital records to examine key features of public hospital spending in England. We describe how costs vary across the life cycle, and the concentration of spending among people and over time. We find that costs per person start to increase after age 50 and escalate after age 70. Spending is highly concentrated in a small section of the population, but the degree of concentration is lower for older age groups. For those aged 25 and under, a third of all hospital spending is accounted for by 1 per cent of the population under 25 and a fifth of spending is accounted for by 1 per cent of patients under 25. For those aged 65 and over, these figures fall to 22 and 13 per cent, respectively. There is persistence in spending over time, with patients with high spending more likely to have spending in subsequent years and those with zero expenditures more likely to remain out of hospital.